Isolated Erythrocytosis Associated With 3 Novel Missense Mutations in the Gene - Joseph A. Moore MD; Maimon E. Hubbi MD, PhD; Chenliang Wang PhD; Yingfei Wang PhD; Weibo Luo PhD; Sandra Hofmann MD, PhD; Siayareh Rambally MD (Journal of Investigative Medicine High Impact Case Reports, 2020)
Hypoxia-inducible factor-1 (HIF-1) is a key regulator of erythropoiesis. In this article, we report 3 novel mutations, P378S, A385T, and G206C, on the EGLN1 gene encoding the negative HIF-1α regulator prolyl hydroxylase domain-2 (PHD2) in 3 patients with isolated erythrocytosis. These mutations impair PHD2 protein stability and partially reduce PHD2 activity, leading to increased HIF-1α protein levels in cultured cells.